TINJAUAN PENERAPAN REKAM MEDIS ELEKTRONIK (RME) RAWAT JALAN MENGGUNAKAN METODE DELONE DAN MCLEAN DI RUMAH SAKIT X - Salsa Bila Tri Cahyaning Tyas; Ilham Rahmansyah; Wiwik Priyatin (Cahaya Ilmu Bangsa Institute, 2025)
Background: RME is an electronic method for collecting, storing, and accessing patient medical records. Every hospital is required to implement Electronic Medical Records (RME), in accordance with the Minister of Health Regulation No. 24 of 2022. Meanwhile, the implementation is still not optimal, seen from the quality of information (information quality), system quality (system quality), service quality (service quality), user influence (actual use), user satisfaction (use satisfaction), net benefits (net benefit). From the preliminary study that has been carried out at Hospital X, it is found that there are several problems related to data that is not stored properly whose output is not in accordance with the user's wishes, thus hampering the performance process of outpatient Electronic Medical Records (RME) users at Hospital X. Method: This study is a quantitative descriptive study using a cross sectional approach. This research was conducted in one of the private hospitals in Central Java. The population in this study included employees who used outpatient RME at Hospital X totaling 33 officers in several units, namely the head of medical records, medical records unit and outpatient registration unit, filling unit, and poly nurse in March-June 2024. The sampling technique was done by total sampling. The instrument in this study used a questionnaire with an assessment using a Likert Scale. Results: The results of the research on the implementation of outpatient electronic medical records have been implemented quite well, system quality with a satisfaction level of 87.9% and RME has been implemented well, information quality with a satisfaction level of 84.8% and RME has been implemented well, service quality with a satisfaction level of 78.8% and RME has been implemented quite well, user satisfaction with a satisfaction level of 78.8% and RME has been implemented quite well, and net benefits with a satisfaction level of 84.8% and RME has been implemented well. Conclusion: The implementation of outpatient Electronic Medical Records (RME) at Hospital X using the Delone and Mclean method regarding system quality variables is implemented well with a satisfaction level of 87.9%, information quality is 84.8%, service quality is 78.8%, user satisfaction variables are 78.8%, and net benefit variables are 84.8% of all total respondents.